2019
DOI: 10.4103/jfmpc.jfmpc_541_19
|View full text |Cite
|
Sign up to set email alerts
|

Skin metastasis from squamous cell carcinoma of the cervix to the lower extremities: Case report and review of the literature

Abstract: Squamous cell carcinoma of cervix commonly metastasizes to the lymph nodes of the pelvis and skin metastasis is a rare presentation even in the late stages of cervical cancer. We report here the first case of cervical cancer with skin metastasis in Saudi Arabia in a 69-year-old female that preceded the diagnosis of cervical carcinoma. Microscopic examination of the skin lesion revealed poorly differentiated squamous cell carcinoma. The patient was in stage IVB based on the International Federation of Gynecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Of these, three presented with cutaneous metastasis which preceded the diagnosis of cervical malignancy, specifically metastatic cervical squamous cell carcinoma and poorly differentiated carcinoma [2][3][4]6]. On review of the literature, four other reported cases have described cutaneous metastasis leading to a diagnosis of cervical cancer since then [7][8][9][10]. All four of these cases described metastatic cervical squamous cell carcinoma.…”
Section: Case Discussionmentioning
confidence: 98%
“…Of these, three presented with cutaneous metastasis which preceded the diagnosis of cervical malignancy, specifically metastatic cervical squamous cell carcinoma and poorly differentiated carcinoma [2][3][4]6]. On review of the literature, four other reported cases have described cutaneous metastasis leading to a diagnosis of cervical cancer since then [7][8][9][10]. All four of these cases described metastatic cervical squamous cell carcinoma.…”
Section: Case Discussionmentioning
confidence: 98%
“…Nodules were the main form [21]. Other clinical manifestations includes maculopapular lesions, scar infiltration, and neoplastic alopecia [23].…”
Section: Discussionmentioning
confidence: 99%